Pesticide Degrading Bacteria in Aquatic Environment: Bioprospecting and Evaluation of Biotechnological Potential - dos Santos, Daniel Rodrigues; de Carvalho, Fátima Cristiane Teles; Abreu, Jade Oliveira; Alves, Carlúcio Roberto; Cavalcante, Rivelino Martins; Vieira, Regine Helena Silva dos Fernandes; de Sousa, Oscarina Viana (Orbital: The Electronic Journal of Chemistry, 2016)
Pesticides play an important role in the increase of productivity in agro-industry and the extensive use of these substances cause environmental, economic and social damage in time. Microbial activity is an essential part in the dynamics and the destination of pesticides in the environment. This research focuses in prospecting and characterizing bacterial strains which are potentially able to degrade/tolerate Atrazine, Chlorpyrifos, Methyl parathion and Picloram. Bacteria were isolated from water samples collected according to the degree of salinity along the Pacoti River’s estuary (Ceara), located in the semi-arid region of northeastern Brazil. A total of 49 bacterial strains were isolated, all of which tolerated/ downgraded concentrations up to 200mg/L of picloram, atrazine and methyl parathion. Tested in pesticide mixtures, the percentage and tolerance level showed that 73% grew in concentrations up to 200mg/L, 17,4% tolerated/ downgraded up to 150ml/L and the remainder only grew in concentrations under 100ml/L. The strains which had the best performance against pesticides, by points, were P1 (13Db e 14D); P2 (10E); P3 (2M, 9M, 10M, 12Mb, 14M, 17M 18Mp 19M e 20M). A high percentage of isolates (67%) expressed luminescence when exposed to the pesticides atrazine and methyl parathion in concentrations between 150 and 200ml/L. DOI: http://dx.doi.org/10.17807/orbital.v8i4.748